2021
DOI: 10.1111/gcb.15680
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon in irrigated agricultural systems: A meta‐analysis

Abstract: Over the last 200 years, conversion of non‐cultivated land for agriculture has substantially reduced global soil organic carbon (SOC) stocks in upper soil layers. Nevertheless, practices such as no‐ or reduced tillage, application of organic soil amendments, and maintenance of continuous cover can increase SOC in agricultural fields. While these management practices have been well studied, the effects on SOC of cropping systems that incorporate irrigation are poorly understood. Given the large, and expanding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 70 publications
(105 reference statements)
3
22
2
Order By: Relevance
“…Otherwise, higher mean SOC stocks before clearing in forest than in perennial crops which is also likely a major contributor to the SOC reduction (Negash et al, 2022). Surprisingly, we found that irrigation did not significantly affect the response of SOC stocks to land clearing, which is inconsistent with studies that have found irrigation in water‐limited systems increases plant productivity and alters the SOC sequestration processes, potentially resulting in a 5.9% increase in SOC stocks (Emde et al, 2021; Wu et al, 2008). We suspect that the effects of irrigation on SOC changes were masked by the lack of consistent irrigation consumption data from the raster layers since only 61 of 242 sampling sites derived from the literature reported irrigation water consumption.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Otherwise, higher mean SOC stocks before clearing in forest than in perennial crops which is also likely a major contributor to the SOC reduction (Negash et al, 2022). Surprisingly, we found that irrigation did not significantly affect the response of SOC stocks to land clearing, which is inconsistent with studies that have found irrigation in water‐limited systems increases plant productivity and alters the SOC sequestration processes, potentially resulting in a 5.9% increase in SOC stocks (Emde et al, 2021; Wu et al, 2008). We suspect that the effects of irrigation on SOC changes were masked by the lack of consistent irrigation consumption data from the raster layers since only 61 of 242 sampling sites derived from the literature reported irrigation water consumption.…”
Section: Discussioncontrasting
confidence: 99%
“…Otherwise, higher mean SOC stocks before clearing in forest than in perennial crops which is also likely a major contributor to the SOC reduction (Negash et al, 2022). Surprisingly, we found that irrigation did not significantly affect the response of SOC stocks to land clearing, which is inconsistent with studies that have found irrigation in water-limited systems increases plant productivity and alters the SOC sequestration processes, potentially resulting in a 5.9% increase in SOC stocks (Emde et al, 2021;.…”
Section: Explaining the Response Of Soc Stocks To Cneccontrasting
confidence: 99%
See 2 more Smart Citations
“…There are also examples showing that combining cover crops and no‐tillage, without exogenous organic inputs, can result in even much larger SOC sequestration rates, for example, in Southern Brazil (Veloso et al, 2018) or in France (Autret et al, 2016). Other practices or systems that can improve SOC levels include agroforestry systems (Cardinael et al, 2018; Corbeels et al, 2019; Mayer et al, 2022), the addition of available exogenous organic matter that would otherwise not be applied to soil (Bruni et al, 2022; Maillard & Angers, 2014), and finally, the removal of soil constraints that result in increased crop productivity and thus C inputs from the crop itself, including roots (Emde et al, 2021; Ladha et al, 2011). Obviously, the impact of these management practices on other greenhouse gas emissions (particularly N 2 O) has to be carefully accounted for.…”
Section: Agronomic Practices To Increase Soil Organic Carbonmentioning
confidence: 99%